Analysis of the Effectiveness of Implementing Accounting Information Systems at PT. Diamond Hevea Industry - Pratiwi, Alfika; Aisyah, Siti (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to analyze the effectiveness of implementing accounting information systems at PT. Diamond Hevea Industry. The research uses qualitative research methods, where this research aims to obtain data that contains. In this research, data collection techniques used observation, interviews and documentation. In this research, the analysis technique used is map analysis, coding map and matrix framework. Based on the results of the analysis of the problem formulation, namely how effective the implementation of the accounting information system at PT. Intan Hevea Industry, then also what obstacles occur in implementing the effectiveness of the accounting information system and finally what efforts are made in implementing the accounting implementation system at PT. Diamond Hevea Industry.